Young skeptics: exploring the perceptions of virtual worlds and the metaverse in generations Y and Z - Korn, Oliver; Zallio, Matteo; Schnitzer, Benjamin (Frontiers in Virtual Reality, 2024)
The Metaverse, a transformation of the internet by XR-technologies progressively blending the digital and physical world, is already changing our social structures. The success of VR-headsets like Quest has made both virtual worlds and the “metaverse” ubiquitous. This technological evolution yields the potential to fundamentally change the way we communicate, live, and work together. At the same time, the perceptions of how these worlds affect our lives differ considerably. To that end, this study investigates the perceptions of 115 younger people from the generations Y and Z, the potential “power users” of virtual worlds. In addition, it investigates differences in perception between non-academics and academics. We looked at perceived knowledge, preferred usage scenarios, interaction with avatars and embodiment, perceived problems and challenges, personal worries, solutions for safeguarding, and institutions to drive safeguarding. While generation Y and Z are often aligned, it is a major finding that in the cases they differ, the younger generation Z is more skeptical. Likewise, non-academics are more skeptical than academics. Finally, we found differences in perception related to gender and provide possible explanations and recommended actions.